An Inquiry into the significance of tithing in the church - Layag, Frank M.
"An inquiry into the significance of tithing in the church is aimed to touch the historical church's teaching on tithing during its first 2000 years."-- Introduction
Includes bibliographical references
A Thesis Presented to the Faculty of Saint Andrew's Theological Seminary, Quezon City
In Partial Fulfillment of the Requirements for the Degree Master in Divinity
Thesis (M.Div)-- Saint Andrew's Theological Seminary